The status of semantic memory in medial temporal lobe amnesia varies with demands on scene construction. (October 2020) - Lynch, Kristin; Keane, Margaret M.; Verfaellie, Mieke
Abstract: Semantic memory is typically preserved in medial temporal lobe (MTL) amnesia. However, there are instances of impairment, such as in the recall of semantic narratives. As some forms of semantic knowledge play out in a spatial context, one possible explanation is that semantic memory impairments, when observed, relate to demands on scene construction – the ability to bind and maintain spatial information in a coherent representation. To investigate whether semantic memory impairments in MTL amnesia can be understood with reference to a deficit in scene construction, the current study examined knowledge of scripts that vary in the extent to which they play out in a scene context in nine patients with MTL amnesia and eighteen healthy control subjects. Scripts are routine activities characterized by an ordered set of actions, including some that are essential for completing the activity. Comparing performance on scene-based scripts (e.g., buying groceries at the grocery store) and object-based scripts (e.g., addressing a letter), we found that patients generated the same number of total action steps as controls for both types of script, but patients were selectively impaired at generating essential actions steps for scene-based scripts. Furthermore, patients made more sequencing and idiosyncratic errors than controls in the scene-based, but not in the object-based, scripts. These findings demonstrate that the hippocampus plays a critical role in the retrieval of semantic knowledge about everyday activities when such retrieval entails scene construction.